Foreign Remittance Inflow in Bangladesh: A Statistical Analysis - Nobi, Md. Nur; Billah, Md. Arif; Jannat, Tani; Shohel, Asaduzzaman (South Asian Review of Business and Administrative Studies (SABAS), 2021)
The major goal of this research is to assess Bangladesh’s foreign remittance inflows In recent years, remittance has risen to prominence as one of the most important economic variables, since it helps with the surplus balance of payments, foreign reserves, aggregate savings, and money circulation After overcoming the negative effects of the COVID-19 pandemic, Bangladesh’s foreign trade has begun to improve In comparison to the previous fiscal year, total export earnings declined by 16 93 percent to US 33,674 09 million in FY 2019-20 During the first half of fiscal year 2020-21, export earnings totaled US 35,180 81 million, up 13 64 % over the same period the previous fiscal year Furthermore, Remittance earnings are growing at a slower rate than emigration from Bangladesh, owing to a rising number of unskilled or semi-skilled laborers in overseas migration rather than professionals Remittances have a great impact on Bangladesh’s economy.